Experimental investigation on a novel arrangement of wet medium for evaporative cooling of air. (April 2021) - Yan, Mingxuan; He, Suoying; Li, Na; Huang, Xiang; Gao, Ming; Xu, Mengfei; Miao, Jiayu; Lu, Yuanshen; Hooman, Kamel; Che, Jianjun; Geng, Zhe; Zhang, Shuzhen
Abstract: A low-speed wind tunnel was designed to experimentally study the cooling performance of a novel arrangement of wet medium for evaporative cooling of air. In the wet medium arrangement (CELdek7060), a 300 mm cooling section was formed by 100 mm wet medium + 100 mm gap + 100 mm wet medium, which will be denoted as 300 mm medium-gap-medium. Normal arrangement was experimentally studied for comparison with medium thicknesses of 100 and 300 mm, respectively. The result shows that the pressure drop of the 300 mm medium-gap-medium is lower than that of the normal medium at thicknesses of 300 mm and is close than that of 200 mm within the tested air speeds, and the cooling effectiveness of the 300 mm medium-gap-medium is higher than that of the normal medium at 200 mm but lower than that of the normal medium at 300 mm. Meanwhile, the correlations of pressure drop and heat transfer coefficient for the 300 mm medium-gap-medium are developed based on the test data. This study proves that the proposed 300 mm medium-gap-medium is feasible and shows superior performance when compared with normal medium at 200 mm thickness.